1987
DOI: 10.1139/v87-390
|View full text |Cite
|
Sign up to set email alerts
|

Formation of oxy radicals by oxygen reduction arising from the surface activity of asbestos

Abstract: . Can. J. Chem. 65, 2338 (1987).Formation of hydroxyl radicals, in relatively large quantities, by oxygen reduction due to the surface activity of asbestos in a cell-free system is demonstrated, using electron spin resonance and a spin trapping agent. The quantity of OH' produced (in general, above l o i 4 mg-I for a Canadian chrysotile) is a function of activation or passivation of the electron donor surface sites of the minerals. The role of these radicals in oxidative stress in relation to the toxic propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
2

Year Published

1990
1990
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(54 citation statements)
references
References 11 publications
3
49
0
2
Order By: Relevance
“…Using cell-free systems, Weitzman and Graceffa (11) showed that a variety of asbestos types can act as catalytic substrates for hydroxyl and superoxide radical generation, apparently from hydrogen peroxide molecules. More recently, Zalma et al (12) published similar studies on oxygen reduction leading to formation of reactive oxygen radicals on asbestos surfaces. The supposition then is that these radicals will injure pulmonary cells and somehow are involved in fibrogenic and possibly carcinogenic (13) mechanisms.…”
Section: Introductionmentioning
confidence: 93%
“…Using cell-free systems, Weitzman and Graceffa (11) showed that a variety of asbestos types can act as catalytic substrates for hydroxyl and superoxide radical generation, apparently from hydrogen peroxide molecules. More recently, Zalma et al (12) published similar studies on oxygen reduction leading to formation of reactive oxygen radicals on asbestos surfaces. The supposition then is that these radicals will injure pulmonary cells and somehow are involved in fibrogenic and possibly carcinogenic (13) mechanisms.…”
Section: Introductionmentioning
confidence: 93%
“…However, contradictory data suggested that nitric oxide is either protective or cytotoxic in acute and chronic phase of inflammatory response, modulation of cytostasis, cell growth and differentiation 29) . Extracellular mechanism of ROS generation is also important with respect to various free radicals formed by interaction of asbestos fibers in cell-free solutions of H 2 O 2 or physiological saline generate superoxide radicals by redox reactions on the fiber surface [31][32][33] .…”
Section: Generation and Release Of Reactive Oxygen Species (Ros) Frommentioning
confidence: 99%
“…Under these circumstances, asbestos-induced cell death is ameliorated. Extracellular mechanisms may also be important in the generation of AOS by asbestos as asbestos fibers in cell-free solutions of H202 or physiological saline generate superoxide (07 and hydroxyl (OH') radicals by redox reactions occurring on the fiber surface (16)(17)(18). Recently, the generation of AOS has been reported by rockwool and glass fibers (19).…”
Section: Studies On Cytotoxicity Of Asbestos and Nonasbestos Fibersmentioning
confidence: 99%